Virtual care as deployed to improve access to primary health care in three Canadian provinces: a policy focused qualitative study - Fleischmann, Adam; Lavergne, Ruth; Leslie, Myles (Université d'Ottawa | University of Ottawa, 2026)
Abstract Background As the COVID-19 pandemic accelerated the uptake of virtual primary care (VPC) in Canada, debates over how it ought to be encouraged or discouraged, governed and paid for have intensified. Within these debates there has been little attention paid to the details of which technologies are being deployed to deliver VPC and how those technologies interact with non-technical factors to ensure efficiency and effectiveness. Methods The aims of the study included drawing out pragmatic considerations for policy makers by identifying the various constellations of VPC technology that are being deployed; characterizing how key informants see them working and to what purpose; and describing how those technologies are interacting with non-technical factors to shape success. 29 qualitative interviews were conducted with mid-level VPC experts from the provinces of Alberta, Nova Scotia, and Ontario. Results Key informants saw a broad range of VPC technologies as improving access to primary care by increasing efficiency and coordination. They deployed VPC to improve the accessibility, availability, and accommodativeness of care. They described VPC technologies interacting with and relying on: human efforts, funding models, and the institutional contexts for their success. Conclusions Policy-makers seeking to optimize VPC will want to consider ways to support not just purchases of technology, but: the human effort required to choose and manage technology; the funding mechanisms that incentivize the efficient use technology; and the institutional contexts and cultures that underpin access improvements through technology.